Environmental Histories of Design: Towards a New Research Agenda. (20th April 2017) - Fallan, Kjetil; Jørgensen, Finn Arne
Abstract: Design and designers hold an ambiguous place in contemporary environmental discourse. They can easily be blamed for causing environmental problems but may also be said to possess some of the competences that could help solve those problems. Design is a fundamental part of the world, where rapidly emerging concepts such as the Anthropocene challenge the distinction between the human-made (or artificial) on the one side and what is not made by human hands (or natural), on the other. Despite the long-standing centrality of design to environmental discourse, and vice versa, deep and systematic 'environmental histories of design' are few and far between. While environmental historians have increasingly explored technology, consumption, and material culture as active agents in discourses of environmental change, they seldom explicitly incorporate design or designers into their studies. At the same time, design history faces a major challenge in accounting for environmental concerns in the history of design discourse. This special issue explores the common ground emerging at the intersection of these two fields of inquiry, with the aim of establishing mutually beneficial understandings upon which to build a new interdisciplinary research agenda.